Penerapan Pendidikan Diniyah Di SDN 24 Kota Banda Aceh - Fadhil Pahlawan; Syaiful Bahri; M. Husen (Program Studi Bimbingan dan Konseling, FKIP Universitas Syiah Kuala, 2020)
This study is entitled the application of Diniyah Education in SDN 24 Banda Aceh City. The purpose of this study is to find out how the implementation of Diniyah education programs in Banda Aceh City SDN 24 and factors that hinder and support the implementation of Diniyah education in Banda Aceh City SDN 24. The approach used is a qualitative approach with descriptive methods. The research location is SDN 24 Kota Banda Aceh. Data collection techniques used are by observation, interview, and documentation. Based on research results obtained that the application of diniyah education in SDN 24 Banda Aceh City is an Islamic-based education to improve student morals so that they have moral values accompanied by good morals of Islamic religious values. In this program, elementary school students are required to master the eight books, namely Masailal Muhtadin, Date, Worship, Uswatun Hasanah, Tauhid, Fardhu'ain, Juz Amma, Prayers of Shalat, Tahsinul Kitab (students taught to read the book), and other materials. The factors that support the implementation of Diniyah education at SDN 24 Banda Aceh City are the enthusiasm and willingness of students who are so happy with Diniyah activities. So this makes it easier for teachers / religious teachers to deliver the material. Second; teaching factors that are able to incorporate learning media (such as learning while playing, singing Islamic songs or blessings so as not to cause students to get bored, able to provide motivation for students. While the inhibiting factors that become obstacles are the absence of syllabus or teaching materials targeted by the education department and the lack of Parental support Some parents are less supportive of diniyah activities, this is evidenced by the lack of interest in attending students during the morning hours.Keywords: Implementation Of Diniyah Education, Primary School ABSTRAK Penelitian ini berjudul penerapan pendidikan diniyah di SDN 24 Kota Banda Aceh. Tujuan penelitian ini yaitu untuk mengetahui bagaimana penerapan program pendidikan diniyah di SDN 24 Kota Banda Aceh dan faktor yang menghambat dan mendukung terlaksananya pendidikan diniyah di SDN 24 Kota Banda Aceh. Pendekatan yang digunakan adalah pendekatan kualitatif dan penelitian deskriptif. lokasi penelitian yaituSDN 24 Kota Banda Aceh. Teknik pengumpulan data yang digunakan adalah dengan cara observasi, wawancaradan dokumentasi. Berdasarkan hasil penelitian yang didapatkan bahwapenerapan pendidikan diniyah di SDN 24 Kota Banda Aceh merupakan pendidikan berbasis Islami untuk memperbaiki akhlak pelajar agar memiliki nilai moral dengan dibarengi akhlak yang baik nilai-nilai agama Islam. Dalam program ini, siswa sekolah dasar dituntut untuk menguasai kitab lapan, yaitu Masailal Muhtadin, Tarikh, Ibadah, Uswatun Hasanah, Tauhid, Fardhu’ain, disamping itu Juz Amma, Do’a Shalat, Tahsinul kitab (siswa di ajari membaca kitab), dan materi-materi lainnya.Faktor yang mendukung terlaksananya pendidikan diniyah di SDN 24 Kota Banda Aceh adanya antusias dan kemauan siswa yang begitu senang dengan kegiatan diniyah. Sehingga ini memudahkan guru/ ustad/ah untuk menyampaikan materi. Kedua; faktor tenaga pengajar yang mampu berkalaborasi dengan media pembelajaran (seperti belajar sambil bermain, menyanyikan lagu Islami atau shalawat sehingga tidak menyebabkan siswa bosan, mampu memberikan motivasi bagi siswa. Sedangkan faktor penghambat yang menjadi kendala yaitu tidak adanya silabus atau bahan ajar yang ditargetkan oleh dinas pendidikan serta kurangnya dukungan orang tua. Sebagian orang tua kurang mendukung kegiatan diniyah, ini dibuktikan dengan kurangnya minat hadir siswa pada saat jam diniyah.Kata Kunci: Penerapan Pendidikan Diniyah, Sekolah Dasar